Clinical implication of the brachial-ankle pulse wave velocity for endovascular treatment - Yoh Arita; Tomoki Fukui; Nobuyuki Ogasawara; Shinji Hasegawa (Indian Heart Journal, 2021)
This study aimed to evaluate the clinical implication of the brachial-ankle pulse wave velocity (baPWV) for endovascular treatment (EVT). Eighty-four patients who underwent EVT for aortoiliac and femoropopliteal artery were included. In these patients, 36 (43 %) had an ABI improvement above 0.9 a day after EVT. The baPWV in patients who received re-EVT afterwards was significantly higher than that of patients who did not. The area under the receiver operating characteristic curve for the baPWV for predicting re-EVT was 0.788. The optimal cut-off values of the baPWV for re-EVT, specificity, and sensitivity were 2220 cm/s, 93.1 %, and 57.1 %, respectively.